Impacts of Ser/Thr Protein Kinase Stk1 on the Proteome, Twitching Motility, and Competitive Advantage in Pseudomonas aeruginosa - Zhu, Xuan; Feng, Chao; Zhou, Lantian; Li, Zhenzhen; Zhang, Yue; Pan, Jianyi (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa is a ubiquitous gram-negative bacterium in the environment and a leading cause of nosocomial infections worldwide. Therefore, it is listed by the World Health Organization as a human pathogen that urgently needs the development of new antibacterial drugs. Recent findings have demonstrated that eukaryote-type Ser/Thr protein kinases play a vital role in regulating various bacterial physiological processes by catalyzing protein phosphorylation. Stk1 has proven to be a Ser/Thr protein kinase in P. aeruginosa. However, the regulatory roles of Stk1 have not yet been revealed. Thus, we constructed a stk1 knockout mutant (∆stk1) from the P. aeruginosa PAO1 strain and employed a TMT labeling-based quantitative proteomic strategy to characterize proteome-wide changes in response to the stk1 knockout. In total, 620 differentially expressed proteins, among which 288 proteins were upregulated and 332 proteins were downregulated, were identified in ∆stk1 compared with P. aeruginosa PAO1. A detailed bioinformatics analysis of these differentially expressed proteins was performed, including GO annotation, protein domain profile, KEGG pathway analysis, subcellular localization and enrichment analysis. Notably, the downregulation of type IV pilus-related proteins and upregulation of T6SS-H1-related proteins were found in the ∆stk1 strain, and the results were corroborated by quantitative PCR at the mRNA level. Further experiments confirmed that the loss of stk1 weakens bacterial twitching motility and promotes a growth competition advantage, which are respectively mediated by type IV pilus-related proteins and T6SS-H1-related proteins. These findings contribute to a better understanding of the physiological role of Stk1, and proteomic data will help further investigations of the roles and mechanisms of Stk1 in P. aeruginosa, although the detailed regulation and mechanism of Stk1 still need to be revealed.